2022
DOI: 10.1155/2022/2973153
|View full text |Cite|
|
Sign up to set email alerts
|

Medicinal Applications of Banana Peel Flour Used as a Substitute for Computing Dietary Fiber for Wheat Flour in the Biscuit Industry

Abstract: The aim of this study, medicinal applications of banana peel flour, was used to estimate nutrition value and minerals content. The results indicated that banana peel flour was safe for food application, and it was lower in protein and fat and higher in dietary fiber and total carbohydrate which were 52.68 and 67.25%, respectively. Moreover, the minerals content of phosphorous, potassium, sodium, manganese, and calcium were 217.92, 110.24, 96.43, 85.25, and 80.27 mg/100 g, respectively. Furthermore, the problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…This finding was supported by Proverawati et al [13] reported that Ambon peel had originally higher dietary fiber content (12.02%) than Kepok (10.44%). Previous study from Alshehry [15] reported a significant increased on dietary fiber of the biscuit with banana peel (ranged from 5.72 -14.19 g) when compared to control (3.65 g). A similar result also found in the used of banana peel powder incorporation into Egyptian balady flat bread.…”
Section: Physicochemical Properties Of Pudding With Banana Peel Additionmentioning
confidence: 90%
See 1 more Smart Citation
“…This finding was supported by Proverawati et al [13] reported that Ambon peel had originally higher dietary fiber content (12.02%) than Kepok (10.44%). Previous study from Alshehry [15] reported a significant increased on dietary fiber of the biscuit with banana peel (ranged from 5.72 -14.19 g) when compared to control (3.65 g). A similar result also found in the used of banana peel powder incorporation into Egyptian balady flat bread.…”
Section: Physicochemical Properties Of Pudding With Banana Peel Additionmentioning
confidence: 90%
“…Banana peels weigh about one-third of the total weight and are reported to contain high nutrients, consisting of 63.82% carbohydrates, 12.67% fiber, 0.89% fat, 3.23% protein, 19.85 mg/100 g calcium, 15.15 mg/100 g iron, 1.72 mg/100 g zinc, and 9.05 mg/100 g manganese [4]. Banana peels also contain vitamin B6, which can lower cholesterol and stabilize metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…The peel is also rich in minerals and dietary fiber. It can, however, be used as an ingredient in healthy or functional foods and banana peel powder has been used to enrich food products (Khoozani et al, 2019;Zaini et al, 2020;Alshehry, 2022). The fiber extracted from banana peel has also recently be used as a supplement in yogurt (Safdari et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%